Increased Risk of Restless Legs Syndrome in Patients With Migraine: A Nationwide Population-Based Cohort Study. Issue 5 (February 2016) - Yang, Fu-Chi; Lin, Te-Yu; Chen, Hsuan-Ju; Lee, Jiunn-Tay; Lin, Chun-Chieh; Huang, Wen-Yen; Chen, Hsin-Hung; Kao, Chia-Hung
Abstract : Abstract: Previous studies suggest that an association between restless legs syndrome (RLS) and migraine exists. However, population-based data are unavailable in Asian cohorts. Our study thus aims to evaluate the association between migraine and RLS in a nationwide, population-based cohort in Taiwan and to examine the effects of age, sex, migraine subtype, and comorbidities on RLS development. Data from the Taiwan National Health Insurance Research Database were used. Patients aged 20 years or older with newly diagnosed migraine from 2000 to 2008 were included; 23, 641 patients with newly diagnosed migraine and 94, 564 subjects without migraine were randomly selected and followed until RLS development, withdrawal from the National Health Insurance, or until the end of 2011. A multivariate Cox proportional hazards regression model was used to explore the risk of RLS in patients with migraine after adjustment for demographic characteristics and comorbidities. Both cohorts were followed for a mean of 7.38 years. After adjustment for covariates, the risk of RLS was 1.42-fold higher (95% confidence interval = 1.13–1.79) in the migraine cohort than in the nonmigraine cohort (7.19 versus 3.42 years per 10, 000 person-years). The increased risk was more prominent in males in the migraine cohort (1.87-fold increased risk, 95% confidence interval 1.22–2.85). Neither comorbidity status nor migraine subtype influenced the RLS risk. This population-based study demonstrated that migraine is associated with an increased risk of RLS compared with those without migraine, particularly in male patients with migraine and regardless of the comorbidity status.